Characterization On Hybrid Circuit For Piezoelectric And Electromagnetic Energy Harvesting From Ambient Vibration Sources - Mat Ali, Noraini (2017)
In this research, a series of experimental analyses for the performance of a hybrid energy harvester is carried out in order to produce an optimum electrical output power. The hybrid energy harvester in this research is an integration of piezoelectric and electromagnetic mechanisms. This research is divided into three main stages. In first stage, characterizations of energy harvesters were studied and hybrid energy harvesting topologies using series and parallel connection are proposed. Characterization was based on resonant frequency, acceleration level and output power. It was found that, series topology of piezoelectric and electromagnetic energy harvester at 25 Hz and 0.5 g level is the best topology compared to parallel topology. In the second stage, diode bridge rectifier and active rectifier were designed and simulations were performed to verify with experimental results. Evaluation was based on rectified electrical output from the energy harvester using two topologies. First topology is piezoelectric and electromagnetic energy harvesters connected in hybrid unit was rectified by sharing the same rectifier circuit and second topology is both of energy harvesters were rectified individually. It was found that piezoelectric and electromagnetic rectified individually using active diode performed a higher output power. The last stage is the integration of hybrid energy harvesting system with active rectifier circuit. Piezoelectric and electromagnetic energy harvester was rectified individually using active diode before both energy harvesters were connected in series topology and fed into capacitor. From the experiment result, it was found that hybrid energy harvesting showed significant improvement in overall performance by producing an optimum electrical output power 100 μW derived at resonant frequency of 25Hz with 0.5 g-level from ambient vibration source.